Average Error: 0.0 → 0.0
Time: 11.4s
Precision: 64
\[\left(1 + x\right) - {x}^{2}\]
\[\left(1 + x\right) - {x}^{2}\]
\left(1 + x\right) - {x}^{2}
\left(1 + x\right) - {x}^{2}
double f(double x) {
        double r3561301 = 1.0;
        double r3561302 = x;
        double r3561303 = r3561301 + r3561302;
        double r3561304 = 2.0;
        double r3561305 = pow(r3561302, r3561304);
        double r3561306 = r3561303 - r3561305;
        return r3561306;
}

double f(double x) {
        double r3561307 = 1.0;
        double r3561308 = x;
        double r3561309 = r3561307 + r3561308;
        double r3561310 = 2.0;
        double r3561311 = pow(r3561308, r3561310);
        double r3561312 = r3561309 - r3561311;
        return r3561312;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[\left(1 + x\right) - {x}^{2}\]
  2. Final simplification0.0

    \[\leadsto \left(1 + x\right) - {x}^{2}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "(1 + x) - x^2"
  :precision binary64
  (- (+ 1 x) (pow x 2)))